2006
DOI: 10.2106/jbjs.d.03042
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Large Lateral Extension of the Acromion with Rotator Cuff Tears

Abstract: A large lateral extension of the acromion appears to be associated with full-thickness tearing of the rotator cuff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
333
5
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(381 citation statements)
references
References 12 publications
27
333
5
16
Order By: Relevance
“…Recently, Nyffeler et al [5] introduced the AI as a new biomechanical value which described the lateral extension of an acromion above the humeral head. They assumed that the force vector of deltoid muscle can increase the joint contraction and may induce subacromial abrasion of the rotator cuff tendons when the acromion extends more laterally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Nyffeler et al [5] introduced the AI as a new biomechanical value which described the lateral extension of an acromion above the humeral head. They assumed that the force vector of deltoid muscle can increase the joint contraction and may induce subacromial abrasion of the rotator cuff tendons when the acromion extends more laterally.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid the influence of the rotation of the scapula or humeral head, the AI was measured on the preoperative oblique coronal MR images done by Nyffeler et al [5] described for a true anteroposterior shoulder radiograph. Each patient was positioned supine with the humerus in neutral rotation and the arm adducted to the side.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with this theory, Anetzberger et al demonstrated an association between lateral projection of both the acromion and coracoid with rotator cuff tears [2]. Similarly, the acromion index, which is expressed as a ratio between the distance from the plane of the glenoid and the lateral edge of the acromion and proximal humerus, has been linked with full thickness rotator cuff tears [9]. Superior migration of the humeral head during abduction may further reduce the supraspinatus outlet area, and has been linked with increasing glenoid inclination according to both biomechanical and computer modelling studies [6,13].…”
Section: Discussionmentioning
confidence: 87%
“…This mechanism, known as the external impingement theory, has since been supported by several studies associating features of scapula morphology with impingement symptoms and rotator cuff tears. These associated features refer to the size and shape of the coracoacromial arch and the orientation of the glenoid, and theoretically lead to a reduction in the functional supraspinatus outlet area [2][3][4][5][6][7][8][9][10][11][12][13][14]. Arthroscopic acromioplasty, which forms the mainstay of surgical management for subacromial impingement syndrome, has been developed in accordance with the external impingement theory.…”
Section: Introductionmentioning
confidence: 99%